1987
DOI: 10.1128/jb.169.9.4061-4067.1987
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the gene for the larvicidal toxin of Bacillus sphaericus 2362: evidence for a family of related sequences

Abstract: During sporulation, Bacillus sphaericus 2362 produces a parasporal crystalline protein which is toxic for the larvae of a number of mosquito species. Using the Eschertichia coli cloning vector Agtll, in which gene products of the inserts may be fused to I8-galactosidase, we isolated 29 bacteriophages which produced peptides reacting with antiserum to crystal protein. On the basis of restriction enzyme analyses of the recombinants and Ouchterlony immunodiffusion experiments with induced lysogens as a source of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 27 publications
1
41
0
1
Order By: Relevance
“…Some of the taxa within B. sphaericus can be distinguished by using test methods based on carbon-source utilization rather than acid production from carbohydrates (de Barjac et al, 1980;Baumann et al, 1984) but the use of such methods alone does not enable complete phenotypic demarcation of the DNA homology groups. The combination of carbon-source utilization tests and other physiological and biochemical characters used in this study has provided a phenotypic classification that is completely compatible with that based on DNA homology and has enabled the separation of several clusters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the taxa within B. sphaericus can be distinguished by using test methods based on carbon-source utilization rather than acid production from carbohydrates (de Barjac et al, 1980;Baumann et al, 1984) but the use of such methods alone does not enable complete phenotypic demarcation of the DNA homology groups. The combination of carbon-source utilization tests and other physiological and biochemical characters used in this study has provided a phenotypic classification that is completely compatible with that based on DNA homology and has enabled the separation of several clusters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fact that the proteins corresponding to the 42-kDa purified toxin from two different potent strains are each active by itself (Baumann et al 1985;Sgarella and Szulmajster 1987) indicates that a transient exposure of the 42-kDa protein to the 51-kDa one may be sufficient to stimulate the toxin activity.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study Broadwell and Baumann (1987) have found that in the larval midguts the 43-kDa protein previously isolated (Baumann et al 1985) is processed to a stable form missing 10 N-terminal and about 20 C-terminal residues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of marine bacteria as a source of biosynthesizing PHA production in marine condition is to avoid contamination from salt-water resistance microbes and marine water is directly filtered and used as industrial large scale medium for production of PHAs [66]. In 1971, 143 marine strains had isolated genus of Beneckea and 3 strains were capable of producing PHB and first ever to be reported from marine source [62]. V. marinofulvus PHB…”
Section: Marine Bacteria Producing Phasmentioning
confidence: 99%